Development of fluorescent nanosensors for real-time biological assays - Elsutohy, Mohamed (2016)
The current advances of nanotechnology in medicine and biology open new horizons towards the development of novel tools (nanosensors) for the detection of several biological compounds, disease biomarkers and cellular molecules. Fluorescent nanosensors are utilised as efficient, rapid and sensitive probes in many analytical and biological applications. The small size of nanosensors enables their insertion into live cells, with minimal cellular disturbance, to detect a specific target within the intracellular environment in real-time. The work described within this thesis outlines the development of fluorescent nanosensors for the detection of cellular and biological markers. Chapter one illustrates a brief introduction for the different types of nanosensors and the methods that are utilised for nanosensor characterisation. Chapter Two describes the development, fabrication and characterisation of size-tuneable ratiometric fluorescent pH nanosensors. The nanosensors were able to detect the pH, one of the most important biological markers, over an extended dynamic range from pH 3.5 to 7.5, encompassing the pH of many biological systems. Chapter Three demonstrates the utilisation of the developed pH nanosensors for the real-time measurement of the intracellular pH of yeast cells, as a model eukaryotic cell, during glucose metabolism. Chapter Four details the study of the process of fluorescence quenching using size controlled core-shell silica nanoparticles. The study showed interesting results for enhanced distance-dependent fluorescence quenching assay using silica nanoparticles. In Chapter Five, aptamer-based fluorescent nanosensors have been developed for the quantitative assay of DNA hybridisation and interferon gamma, a model cytokine.